The Silent Masters : Latin Literature and Its Censors in the High Middle Ages - Godman, Peter (Book collections on Project MUSE., 2000)
In the tension between competing ideas of authority and the urge to literary experiment, writers of the High Middle Ages produced some of their most distinctive achievements. This book examines these themes in the high culture of Western Europe during the eleventh and twelfth centuries, showing how the intimate links between the writer and the censor, the inquisitor and the intellectual developed from metaphors, at the beginning of the period, to institutions at its end. All Latin texts--from Peter Abelard to Bernard of Clairvaux, from the Archpoet to John of Salisbury and Alan of Lille--are.